L'art et le livre. - Butor, Michel; Canonne, Xavier; Delattre-Druet, Marie-Blanche; Foulon, Pierre-Jean; Gilmont, Jean-François; Maury, Pierre; Moeglin-Delcroix, Anne; Schraenen, Guy; Vandevivere, Ignace; van Leeuwen, Jan Storm (Morlanwelz : Musée royal de Mariemont, 1988)
Kosuth, Joseph ; Moeglin-Delcroix, Anne ; De Samblanx, Charles ; Lecuire, Pierre ; Delahaut, Jo ; Pistoletto, Michelangelo ; Gac, Jean Le ; Chia, Sandro ; Clemente, Francesco ; Cucchi, Enzo ; De Maria, Nicola ; Ontani, Luigi ; Paladino, Mimmo ; Nannucci, Maurizio ; Perec, Georges ; Alberola, Jean-Michel ; Daive, Jean ; Sauze, Max ; Soffici, Ardengo ; Duchamp, Marcel ; Broodthaers, Marcel ; Magritte, René ; Vostell, Wolf ; Debliquy, Marie-Line
L'art et le livre, Musée royal de Mariemont, Morlanwelz, du 12 décembre 1986 au 1er mars 1987
Frans & Nederlands
boek